From miracle to mediocrity? Explaining the growth slowdown of the Korean economy - Duyong Kangand; Sungkeun Park (KDI Journal of Economic Policy, 2023)
To investigate the causes of Korea's growth slowdown over the past thirty years, we estimate the contributions of major developmental factors, including i) demographic factors (changes in population growth and workforce age due to the demographic transition), ii) quality-of-life-related choice factors (changes in working hours, education, and the female employment rate), iii) structural change, and iv) the effects of productivity catch-up. Our estimates show that these four groups of factors account for approximately 90 percent of the growth slowdown, with demographic factors contributing approximately 30 percent and the other three groups of factors each contributing about 20 percent. We also show that the same factors explain most of Korea's high growth in the 1980s. These results suggest that Korea's growth slowdown is basically a consequence of its successful economic development and that the high growth and subsequent slowdown can be regarded as a single process. In addition, given that the factors examined here exhibit similar patterns of change in the course of economic development of most countries, we think that our estimation results of the relationship between economic development and changes in economic growth trends could have more general implications that go beyond Korea's experience.
Keywords: O47; O11; O53; 330; Economic Growth; Slowdown; Korean Economy; Economic Development